PENGARUH KUALITASPELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN HANDPHONE SAMSUNG - Nel Arianty (JURNAL ILMIAH MANAJEMEN & BISNIS, 2015)
The approach used in this research is associative which is one type of explanation which is a research study that aims to determine the relationship between two or more variables. This research was conducted at the University of North Sumatra Muhammadiyah location at Jl. Muchtar Captain Basri Medan. In this case the study population are all consumers of Android-based Samsung mobile phone users with no measurable amount. The sample in this study 100 consumer Samsung Android-based mobile phone users. Based on the research results it can be concluded service quality affects customer satisfaction samsung mobile phones. Product quality to customer satisfaction samsung mobile phones. From the calculation, that the quality of product and service quality affects customer satisfaction. The most dominant variable effect on customer satisfaction is the variable quality of service.Keywords: Service Quality, Product Quality and Customer Satisfaction.